2014
DOI: 10.1093/rpd/ncu338
|View full text |Cite
|
Sign up to set email alerts
|

Radiation exposure to caregivers from patients undergoing common radionuclide therapies: a review

Abstract: The contribution of radionuclide therapies (RNTs) to effective patient treatment is widely appreciated. The administration of high doses has necessitated investigating the potential radiation hazard to caregivers from patients undergoing RNTs. This work aimed to review the literature regarding measured effective doses to caregivers from such patients. The main selection criterion was the presence of real radiation exposure measurements. The results were categorised according to the treatment protocol and dose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
7
0
1
Order By: Relevance
“…While other radionuclides have been studied for treating peritoneal metastasis with origin from ovarian cancer, such as 90 Y-HMFG1 and 211 At-MX35-F(ab’) 2 being two of the candidates ( 11 , 12 ), we have not been able to find radiation protection publications related to these treatments. Stefanoyiannis et al ( 13 ) compared studies examining radiation exposure to caregivers from patients for different common radionuclide therapies. These included radiopharmaceuticals with iodine-131 ( 131 I), yttrium-90 ( 90 Y) and lutetium-177 ( 177 Lu).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While other radionuclides have been studied for treating peritoneal metastasis with origin from ovarian cancer, such as 90 Y-HMFG1 and 211 At-MX35-F(ab’) 2 being two of the candidates ( 11 , 12 ), we have not been able to find radiation protection publications related to these treatments. Stefanoyiannis et al ( 13 ) compared studies examining radiation exposure to caregivers from patients for different common radionuclide therapies. These included radiopharmaceuticals with iodine-131 ( 131 I), yttrium-90 ( 90 Y) and lutetium-177 ( 177 Lu).…”
Section: Discussionmentioning
confidence: 99%
“…Although amounts of activity should not be directly compared in most circumstances, it is worth mentioning that in the case of 224 Ra-CaCO 3 -MP, an activity of three or four orders of magnitude lower (7 MBq) is used. In summary, Stefanoyiannis et al found that the doses was within the dose constraints of 5 mSv to home caregivers, recommended by the International Commission of Radiological Protection (ICRP)(13). They also highlighted the importance of giving specific instructions to caregivers, as the highest dose values were found when no instructions were given.The standard activity dosage of 223 RaCl 2 is 55 MBq/kg body weight given intravenously in six administrations 4 weeks apart(14).…”
mentioning
confidence: 94%
“…[ 12 ] Outpatient-based remnant thyroid ablation with I-131 (1,110 MBq) performed in patients with DTC could be a safe alternative if applied under experts' appropriate supervision and guidance. [ 9 10 ] Despite poor compliance with safety guidelines, a short-stay protocol respects current legislation and applies to most patients treated with 3.7 GBq. [ 19 ] Higher body weight and distant metastases may predict higher radiation exposure from patients after RAI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…An outpatient treatment results in a minimal dose to the family members if the patient's families could comply with statutory dose limits and restrictions. [ 8 9 10 11 ] It could be more cost effective and has better patient acceptance. [ 12 ]…”
Section: Introductionmentioning
confidence: 99%
“…This result concurs with the literature. Data were provided on the effect of various radionuclide therapies on the exposure of relatives [16], ranging from 0.1-3.08 mSv. In another study by Matheud et al [17] similar effective doses for relatives and other groups of people (employees, traveling companions) are listed, the range is given as 0.3 mSv to 3 mSv.…”
Section: Diseasementioning
confidence: 99%